Learning C# by Developing Games with Unity 2021 : Kickstart Your C# Programming and Unity Journey by Building 3D Games from Scratch, 6th Edition. - Ferrone, Harrison (Packt Publishing, Limited, 2021)
This sixth edition of the popular C# guide helps you learn the building blocks of the C# language, right from variables to classes and exception handling. After getting to grips with the basics of C# programming, it takes you through the world of Unity game development and how you can apply C# knowledge using game development examples.